Estudo numérico do comportamento térmico do conjunto laje-viga de concreto sujeito a incêndio localizado - Toassi, Tobias Luiz Marchioro (2020)
This work aims to analyze the heat transfer in concrete structures. It is estimated thataround R$ 750M is lost annually due to fires involving concrete structures in Brazil.The main goal of the present work is perform the simulation of a fire in a parking lot, inorder to obtain the temperature over the time of the concrete. The convective-diffusiveheat transfer problem is solved through the discretization of the governing differentialequations through the finite volume method, where the linear systems generated by thediscretization are solved using non-stationary and preconditioned iterative techniques.Two-dimensional and three-dimensional simulations were performed, variating betweendifferent values of concrete thermal conductivity and also performing simulations withk−εandLESturbulence models. Two beam types were numerically simulated, a steelprofile and a concrete rectangular profile. The steel beam case was used to comparethe values of the interest properties and verify the numerical configuration neglectedin the present work. While the case of the concrete beam represents a situation closeto what is actually seen in practice. The results obtained in the present work basicallyconsist of the property fields related to the solution domain subject to the localizedfire, that is, the scalar fields (density, pressure, temperature) and vector (speed) forthe air and the temperature distribution at over the time of the slab/beam assembly.Different behaviors of temperature were observed in the concrete with changes in thethermal conductivity, which are consistent with the order of magnitude of the properties,in addition to a low influence on the temperature of the concrete among the turbulencemodels used in this work.